Time course of safety and efficacy of aflibercept in combination with FOLFIRI in patients with metastatic colorectal cancer who progressed on previous oxaliplatin-based therapy - Ruff, Paul; Ferry, David R; Lakomỳ, Radek; Prausová, Jana; Van Hazel, Guy A; Hoff, Paulo M; Cunningham, David; Arnold, Dirk; Schmoll, Hans J; Moiseyenko, Vladimir M; McKendrick, Joseph J; Ten Tije, Albert J; et al. (European journal of cancer (Oxford, England, 2015)
BACKGROUND: Patients with metastatic colorectal cancer (mCRC) previously-treated with oxaliplatin benefit significantly from the addition of aflibercept to FOLFIRI in relation to overall survival, progression-free survival and response rate. PATIENTS AND METHODS: The results for efficacy and safety over the time course of the VEGF Trap (aflibercept) with irinotecan in colorectal cancer after failure of oxaliplatin regimen trial were analysed based on data from 1226 patients randomised to receive FOLFIRI plus either aflibercept (n=612) or placebo (n=614). Hazard ratios (HR) by 6-month time period were estimated using a piecewise Cox proportional hazard model. Severity of adverse events (AEs) was graded using National Cancer Institute Common Terminology Criteria, version 3.0. RESULTS: The estimated probabilities of survival were 38.5% versus 30.9% at 18 months, 28.0% versus 18.7% at 24 months and 22.3% versus 12.0% at 30 months, for the aflibercept- and placebo-treated arms, respectively. The proportional improvement in the HR over time was consistent with the survival probability results; survival at 24 months was improved by 50% and almost doubled at 30 months. The majority of worst-grade AEs occurred within the first four cycles of treatment and in a small percent of treatment cycles and were mostly reversible. Common chemotherapy- and anti-vascular epithelial growth factor (VEGF)-associated AEs occurred rarely and in a small proportion of cycles with the majority being of single occurrence. CONCLUSIONS: The addition of aflibercept to FOLFIRI showed a continued and persistent improvement in overall survival over time in patients with mCRC. Although grade 3-4 AEs were more frequent in the aflibercept arm, they occurred in early treatment cycles and decreased sharply following initial presentation.
Keywords: metastázy nádorů; proporcionální rizikové modely; Proportional Hazards Models; biomarkery farmakologické; Disease Progression; VEGF-A; Oxaliplatin; kolorektální nádory; oxaliplatin; Efficacy; progrese nemoci; fluoruracil; Fluorouracil; VEGF-B; kamptothecin; Colorectal Neoplasms; mužské pohlaví; Biomarkers, Pharmacological; Organoplatinum Compounds; Camptothecin; Receptors, Vascular Endothelial Growth Factor; receptory vaskulárního endoteliálního růstového faktoru; Irinotecan; Aflibercept; Safety; Neoplasm Metastasis; Disease-Free Survival; ženské pohlaví; Colorectal cancer; Humans; organoplatinové sloučeniny; irinotekan; Leucovorin; leukovorin; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; PlGF; Female; přežití bez známek nemoci; lidé; Male